2020
DOI: 10.3390/app10041515
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Seismic Fragility Analysis for Large-Scale Piping System Utilizing Bayesian Approach

Abstract: In the event of an earthquake, it is essential to accurately assess the seismic fragility of piping systems to ensure the continued safety of society. When evaluating the seismic fragility of a piping system, which is generally a secondary structural system, this should mainly be an integrated model that includes both the primary structural frames and the secondary ones, unlike the primary structural system of a building. Hence, the piping seismic fragility evaluation has an issue in that it takes considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, Bursi et al (26) showed that a typical petrochemical piping system coupled with a steel support structure is endowed with a limited q factor, because both pipes and the support floors cannot ensure a rigid floor behavior and a great involvement of dissipative elements. In addition, (27) and (28) demonstrated that the response of a piping system can be greatly reduced by including the nonlinear behaviour of local supports.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Moreover, Bursi et al (26) showed that a typical petrochemical piping system coupled with a steel support structure is endowed with a limited q factor, because both pipes and the support floors cannot ensure a rigid floor behavior and a great involvement of dissipative elements. In addition, (27) and (28) demonstrated that the response of a piping system can be greatly reduced by including the nonlinear behaviour of local supports.…”
Section: Background and Motivationmentioning
confidence: 99%
“…u represent the vertical load from the upper structure, radius of curvature of the curved surface, horizontal displacement, surface friction coefficient, and velocity, respectively. The natural period of the FPS can be determined by R, regardless of the upper structure mass, according to Equation (2).…”
Section: Friction Pendulum Systemmentioning
confidence: 99%
“…Recently, nonstructural systems, such as mechanical and electrical equipment, suffered relatively extensive damage during strong ground motion, even when the primary system had no structural damage [1]. In addition, in moderate seismic zones, such as the Korean Peninsula, earthquake damage is concentrated on nonstructural components; nonstructural earthquake damage, including damage to electrical equipment and piping systems, was observed in the 2016 Gyeongju and 2017 Pohang earthquakes in Korea [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the start of monitoring and measuring earthquake motions in 1978, earthquakes in Korea with a moment magnitude of 2.0 or higher have occurred 20 times per year until 1998, but this frequency has increased to an average of 48 times per year during the period between 1998 and 2015 [3]. Furthermore, Korea has experienced two strong earthquakes, one in Gyeongju in 2016 and the other in Pohang in 2017, raising concerns over safety during earthquakes near major facilities [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%